The Effectiveness of a Brief Sexuality Education Intervention for Parents of Children with Intellectual and Developmental Disabilities. Issue 4 (1st October 2020) - Rooks-Ellis, Deborah L.; Jones, Brooklin; Sulinski, Ella; Howorth, Sarah; Achey, Nicole
Abstract: Parents are often responsible for educating their child about sexuality and relationships, yet many parents may not be aware of the sexuality-related topics to teach. Sexuality education is critical for children with autism and intellectual disabilities, who are often vulnerable to sexual abuse and other sexual behavior outcomes. Families teaching sexuality can help their child learn about healthy hygiene, interactions, and relationships. The purpose of this study was to implement a brief sexuality education training for parents and caregivers who have children diagnosed with intellectual and developmental disabilities, including autism. A Wilcoxon-signed rank test revealed a statistically significant change in parents' (1) attitudes and beliefs, (2) level of communication, and (3) competence to teach sexuality topics following participation in the sexuality education training program. Strategies were provided to assist parents in effectively providing sexuality information to their child with intellectual and developmental disabilities. Educators are urged to increase their awareness of this unmet need and to partner with families to implement strategies that promote the physical, emotional, and social independence of individuals with autism and intellectual disabilities.